Помогите решить lg(2x+1)*lg(x-1)=lg(x-1)

Помогите решить lg(2x+1)*lg(x-1)=lg(x-1)
Гость
Ответ(ы) на вопрос:
Гость
[latex]lg(2x+1)*lg(x-1)=lg(x-1)[/latex] ОДЗ: [latex]\begin{cases}2x+1>0\\x-1>0\end{cases}<=>\begin{cases}x>-0,5\\x>1\end{cases}\\\\x\in(1;+\infty)[/latex] [latex]lg(2x+1)*lg(x-1)-lg(x-1)=0\\lg(x-1)*(lg(2x+1)-lg10)=0\\lg(x-1)=0\ \ \ \ lg(2x+1)-lg10=0\\x-1=1\ \ \ \ \ \ \ \ \ \frac{2x+1}{10}=0\\x=2 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 2x+1=0\\. \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=-0,5[/latex] По ОДЗ ответ х=-0,5 не подходит,значит ответ х=2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы